Determinants of Economic Growth in a Resource-Dependent Economy: An Endogenous Approach to Libya (1990–2023) (Comprehensive Journal of Science, 2026)
This study investigates the primary determinants of economic growth in Libya from 1990 to 2023 through the lens of endogenous growth theory. Utilizing an Autoregressive Distributed Lag (ARDL) bounds testing approach, the research empirically evaluates the short- and long-run impacts of macroeconomic variables—including Foreign Direct Investment (FDI), inflation, government expenditure, trade openness, gross fixed capital formation (GFCF), and oil prices—on real GDP growth. The empirical findings reveal that while trade openness and oil prices exert a statistically significant positive effect on economic expansion, variables such as government expenditure, GFCF, and FDI present counterintuitive negative coefficients. These results underscore the severe structural inefficiencies, institutional deficits, and "resource curse" phenomena prevalent in the Libyan economy. The paper concludes that to achieve sustainable endogenous growth, Libya must transcend its heavy reliance on hydrocarbon revenues by improving institutional quality, redirecting public expenditure toward human capital and R&D, and creating an absorptive environment for productive capital spillovers.
Keywords: Endogenous Growth, ARDL Model, Libyan Economy, Foreign Direct Investment, Macroeconomic Determinants, Resource Curse